The Attitudes of Nursing Students towards Patients Who Attempt Suicide: A Study from Central India - Ghormode, Deepak; Gupta, Pramod; Singh, S. K.; Ratnani, Devendra (International Journal of Innovative Research in Medical Science, 2018)
Background: Suicide being a global health issue, the attitudes and beliefs of the healthcare professionals towards these attempters have significant effect on the outcome of the treatment. Objectives: Aim of the study was to assess the attitude of nursing students towards patients with suicide attempt. Materials and Methods: The study had a cross sectional design of 284 nursing students who were randomly recruited from the two institutions. Suicide opinion Questionnaire was administered. Results: Most were young single females, from rural locality, who were pursuing either BSc Nursing or GNM courses. Very few had previous exposure to suicide prevention training programmes. More than half of the students showed favourable attitude towards patients with suicidal attempt. Majority of students showed favourable attitudes for more than half of the attitudinal statements giving importance to the mental illness, disturbed family life, and depression and risk factors for suicide attempt. Unfavourable and uncertain attitude was noticed for a few of the statements. Conclusions: The nursing students showed favourable attitude towards patients with suicide attempts. More educational and training programs are therefore needed in these students for improving the uncertain and unfavourable responses to a few of these attitudes for better management of these patients.